(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
High-frequency trading (HFT) systems generate and process vast volumes of financial data in real time, demanding scalable and efficient algorithms for data analysis. This study presents a comparative investigation of classical indexing techniques and modern stream processing algorithms for HFT data analysis